Effect of habitat and age on variations in volatile organic compound (VOC) emissions from Quercus ilex and Pinus pinea (Atmospheric Environment, 1997)
A dynamic branch enclosure was used to measure emission rates of volatile organic compounds (VOCs) under field conditions from two common native Mediterranean species, Quercus ilex and Pinus pinea. In addition to a-pinene, B-pinene, sabinene, limonene and cineole, a suite of lesser known compounds were tentatively identified including cis- and trans-ocimene, cis- and trans-linalool oxide and sabinaketone. Emissions of isoprene from Quercus ilex were insignificant in comparison to those of the monoterpenes and were not detected from Pinus pinea. Variability in emission rates between two habitats, the forest and the dunes, were assessed for Quercus ibex. Temperature sensitivities of emissions and total summed emission rates from Quercus ilex were clearly related to environmental conditions. Emission rates from Pinus pinea showed great variability, but differences between normalised mean emission rates from mature forest and young plantation trees may be significant. Existing emission rate models were found to inadequately describe the observed data.

Screening of 18 Mediterranean plant species for volatile organic compound emissions (Atmospheric Environment, 1997)
Eighteen tree and shrub species were screened for emissions of isoprene and other volatile organic compounds (VOCs) at three locations at Castelporziano (Italy) using a bag-enclosure sampling method followed by GC analysis. Thirty emitted compounds were identified. Temperature sensitivity of emissions of monoterpenes varied between species. Strong temperature dependencies were found for isoprene emissions. For monoterpene-emitting plant species with greatest ground cover in the dunes and macchia habitats, α-pinene, β-pinene and sabinene appeared to be the most frequently and abundantly emitted compounds. Isoprene was the major emission from the shrub species screened in the forest. Emissions from four dominant plant species were scaled up to estimate total fluxes from the dunes and macchia over a daytime period. Species with greatest biomass but low emission rates made a substantial contribution to total emissions.